Evaluation and Analysis of Environmental Noise Pollution in Seven Major Cities of India - Naveen GARG; A. K. SINHA; M. DAHIYA; V. GANDHI; R. M. BHARDWAJ; A. B. AKOLKAR (Archives of Acoustics)
The paper describes the noise monitoring data acquired from the pilot project on the establishment of National Ambient Noise Monitoring Network (NANMN) across seven major cities in India for continuous noise monitoring throughout the year. The annual average Lday (06-22h) and Lnight (22-06 h) values observed in year 2011-2014 for the 35 locations under study in which 14 locations are in commercial zone, 5 in Industrial, 7 in residential and 9 in silence zones are described. The long-term noise monitoring shows that ambient noise levels have marginally increased for 29 sites (82.9%) since past four years. The present study is focussed on evaluation and analysis of environmental noise pollution at 35 noise monitoring sites in seven major cities of India and shall be instrumental in planning for the noise abatement measures for controlling the noise pollution in these sites.